Antibiotic Susceptibility Pattern Among Cancer Patients with Urinary Tract Infection at a Tertiary Cancer Hospital in Nepal - Adhikari, Abish; Pandit, Subhas; Sapkota, Simit; Bhandari, Jeebana; Suwal, Atul (Purbanchal University Health Journal, 2024)
Background: Cancer patients are at a higher risk of infection due to the nature of treatment modalities used that lead to immunosuppression. Urinary tract infections are the most common cause of morbidity among cancer patients. Objective: The objective of this study is to determine antibiotic sensitivity and resistance pattern in cancer patients with urinary tract infections at a tertiary cancer hospital in Nepal. Method: A retrospective analysis was conducted on cancer patients with urinary tract infections from September 2020 to June 2024 at a tertiary cancer hospital in Nepal. Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method. Data on positive urine cultures were extracted from the medical laboratory system. Bacterial profiles and antibiotic susceptibility test results were assessed. Data were analyzed using R-statistical software. Result: A total of 613 urine cultures were performed during the study period among which 116 were positive cultures. After excluding ineligible cultures, 102 (16.63%) positive cultures from 97 patients were included. Most of the patients were females (79.38%). The most common cancers were gynecological (43.39%) followed by genitourinary (9.28%), central nervous system (9.28%) and lung (8.25%) cancers. The most isolated bacteria were Escherichia coli (62.88%) followed by Klebsiella pneumonia (14.43%). The most sensitive antibiotics were Amikacin (68.42%), Nitrofurantoin (63.54%), Gentamicin (41.43%), Co-trimoxazole (40.63%), Ofloxacin (38.10%), Amoxicillin/Clavulanate (31.51%), Norfloxacin (26.09%), Ciprofloxacin (20.93%), Cefixime (13.85%) and Amoxicillin (8.33%) while the antibiotics in reverse order were most resistant antibiotics among top 10 tested antibiotics. Conclusion: The findings of this study can guide clinicians to make an informed decision in the selection of antibiotics and management of urinary tract infections in cancer patients.